On the Dynamics of a SEIHR Model With Delays in Diagnosis and a Class of General Incidence Functions - Ali Traoré; Fourtoua Victorien Konané (Journal of Mathematics)
The susceptible, exposed, infectious, hospitalized, and recovered (SEIHR) model with delays in diagnosis is investigated. A class of general incidence functions is considered. The threshold for the model is determined, and the stabilities of the equilibrium points are examined. The effects of the delay in diagnosis on the spread of the disease are studied. A comparative study between the delay-induced basic reproduction number Rϕ for the model and the basic reproduction number R0 when the infection is timely diagnosed is performed.